A Review on the Mechanism of Tuina Promoting the Recovery of Peripheral Nerve Injury. (5th July 2021) - Liu, Zhifeng; Wang, Hourong; Yu, Tianyuan; Jiao, Yi; Zhang, Yingqi; Liu, Di; Xu, Yajing; Guan, Qian; Lu, Mengqian
Abstract : Tuina, as one of the characteristic external therapies of Traditional Chinese Medicine (TCM), has been used to treat the disease caused by peripheral nerve injury (PNI) for thousands of years. An increasing number of clinical trials and animal experiments have demonstrated that tuina can improve the symptoms and promote the recovery of damaged nerves. This review focuses on the mechanistic studies of tuina in promoting the recovery of PNI, which might provide a neurobiological foundation for the effects of tuina. Although many mechanisms underlying the effects of tuina on nerve repair have been identified, there are still many unknown problems, such as the key substance or way for tuina to work, so further investigation is warranted.